Burning suicide attempts in women - Jamile de Sousa Pacheco; Ana Kelve de Castro Damasceno; Ângela Maria Alves e Souza; Maria Eliane Macielde Brito (Rev Rene)
Burns are potential serious traumas, because, although the morbid mortality rates are high, they may lead to psychological and social outcomes. The study aimed to identify the cases of burning suicide attempts in women in a burned treatment center; describe these women’s socioeconomic profile and evaluate the factors related to the suicide attempt. It is an exploratory, qualitative and prospective study. The data were collected at the Burned Treatment Center (BTC) at the hospital in studied through questionnaire and opened questions with four women. It was found out that most cases were with teenagers and young adults who did not have a stable union. Depression, matrimonial issues and mourning were the main reasons for the suicide attempts. The suicide attempt is an act which is more consummated by women. Once they are considered more vulnerable, they are more susceptible to take such a decision.